Research productivity of the state universities of Sri Lanka, a case based on SciVal and the contribution of the libraries towards excellence - Wijetunge, Pradeepa; Silva, M.A.L.; Manatunga, P.K.S. (My University, 2020)
This paper discusses the research productivity of five state universities of Sri Lanka during 2015-2018, using scholarly output, citation impact and collaboration metrics of SciVal, and the contribution of the university libraries towards research excellence. Five multi-disciplinary state universities; University of Colombo (UoC), Kelaniya (UoK), Peradeniya (UoP), Ruhuna (UoR) and Sri Jayewardenepura (UoSJP) were selected as the sample. During the study period, 4723 publications and 3831 authors have been recorded, of which UoC and UoP records the highest numbers. UoR records the highest publications in top journal percentile and highest number of views (72) among the five universities. A total of 33104 citations are reported while UoP depicts the highest citation count (18322) as an individual university, while UoR records the highest h5-index (39). Highest Field Weighted Citation Impact (3.18) and the highest citations per publication (12.4) is recorded by UoP while the highest output in top citation percentile (32.5%) is recorded by UoR. UoR records the highest overall international collaboration (74.4) during the studied period and UoP records the highest academic/corporate collaboration (2.2). University libraries provide collections and conducive environments for researchers, training in searching for information, referencing styles and use of reference management software, plagiarism detection and they maintain Institutional Repositories. The study established that there is much scope for university libraries to expand the services to support research productivity and recommends that librarians should consider on more current support areas like research data management, measuring research impact, and digital curation in order to support their universities to achieve excellence in research productivity.
Keywords: Citation Impact, Collaboration, Scholarly output, Sri Lanka, State Universities, SciVAL, Research Productivity